Intelligent systems and smart infrastructure : proceedings of ICISSI 2022 - International Conference on Intelligent Systems and Smart Infrastructure (2022 : Prayagraj, India); Mishra, Brijesh; Wairya, Subodh; Tiwari, Manish; Singh, Rakesh Kumar (Boca Raton : CRC Press, 2022)
This book covers the proceedings of ICISSI 2022 (International Conference on Intelligent Systems and Smart Infrastructure) held atPrayagraj, Uttar Pradesh during April 21-22, 2022. The conference was jointly organised by Shambhunath Institute of Engineering and Technology, Prayagraj UP India, Institute of Engineering and Technology (IET) Lucknow, U.P India, and Manipal University Jaipur, Rajasthan India with an aim to provide a platform for researchers, scientists, technocrats, academicians and engineers to exchange their innovative ideas and new challenges being faced in the field of emerging technologies. The papers presented in the conference have been compiled in form of chapters to focus on the core technological developments in the emerging fields like machine learning, intelligence systems, smart infrastructure, advanced power technology etc.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Congresses; Artificial intelligence -- Industrial applications -- Congresses; COMPUTERS / Management Information Systems; COMPUTERS / Database Management / General; TECHNOLOGY / General